Liposome Based Drug Delivery for the Management of Psoriasis - A Comprehensive Review - Bahadur, Shiv; Sharma, Manisha (Current Pharmaceutical Biotechnology, 2023)
Psoriasis has been considered as a chronic inflammatory skin disease which leads to the dysfunction of immune systems. According to the World Psoriasis Day consortium, psoriasis affects around 125 million individuals globally or about 2% to 3% of the overall population. Most of the conventional drug delivery systems primarily attempt to relieve symptoms of psoriasis and are ineffective in providing targeted action and higher bioavailability because of the drug's short half-life and instability, as well as they lack safety and efficacy. The shortcomings of conventional drug delivery systems give rise to the development of novel drug delivery systems which includes liposomes, transferosomes, ethosomes, niosomes, emulsomes, dendrimers, hydrogel, nanoparticles, etc. These novel formulations may enhance the therapeutic effects by changing physiological and pharmacokinetic parameters. Several research reports suggest that these novel drug delivery systems may enhance therapeutic effects which can be used as a promising approach for the treatment of psoriasis. The liposomes based drug delivery system have been considered as most promising vehicles for enhancing therapeutic potentials of drugs into or through the skin upon topical application. Liposomes have small unilamellar vesicles which may enhance the penetration ability through stratum corneum layer of skin. Therefore, present review article highlights on the different aspects of the liposomes as potential drug delivery system for the treatment of psoriasis.
Keywords: drug delivery